MANAJEMEN MASJID PADA MASA PANDEMI COVID 19 - Nurseri Hasnah Nasution; Wijaya Wijaya (Yonetim Jurnal, 2020)
The function of the mosque is very significant to human life, so that the mosque is very crowded with people, especially at certain times. The congregation that visits the mosque most is the male congregation. Meanwhile, men are a group that is vulnerable to covid-19. This condition is a potential distribution and transmission of covid-19. For this reason, there is a need for mosque management based on health transitions during the co-19 pandemic. The aim is to prevent and break the chain of distribution of covid-19. This management incorporates elements of social conception and behavior change in relation to health determinants. This management includes: first, physical management consisting of management, construction and physical maintenance ofmosques, maintenance of mosque cleanliness, management of mosque facilities. Second, functional management which includes the function of the mosque as a place of propaganda, a place of education, and a place for socialization and information about preventing the spread of covid-19. Keywords: Management, Mosque, Covid Pandemic 19.